The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/ijshe-08-2019-0241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a tertiary sustainability experiential learning program

Abstract: Purpose This paper aims to describe the development, promotion and evaluation of sustainability learning experience database (SLED), a university-curated database of sustainability experiences to augment formal student learning. Its purpose was to encourage students to participate in experiential learning, to facilitate students’ critical appraisal of programs ostensibly designed to create sustainability and to, thus, develop students’ sustainability self-efficacy and employability. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…en, the evaluation index system of teaching quality is established by referring to relevant literature and research and adopting AHP [28][29][30]. e evaluation index system of Wushu teaching quality is established through AHP, but these indexes have multiple collinearity and serious information redundancy.…”
Section: Fuzzy Clustering Methods Of Wushu Teaching Datamentioning
confidence: 99%
“…en, the evaluation index system of teaching quality is established by referring to relevant literature and research and adopting AHP [28][29][30]. e evaluation index system of Wushu teaching quality is established through AHP, but these indexes have multiple collinearity and serious information redundancy.…”
Section: Fuzzy Clustering Methods Of Wushu Teaching Datamentioning
confidence: 99%
“…Based on experience, use 1 to 9 as the corresponding judgment matrix scale [24]. e judgment matrix scale is as follows: when the scale is 1, it means i and j are equally important; when the scale is 3, it means that i is slightly more important than j; when the scale is 5, it means that i is significantly more important than B; when the scale is 7, it means that i is very important than j; when the scale is 9, it means that A is extremely important than j; when the scale is 2, 4, 6, 8, i and j are in the middle of two adjacent judgments [25][26][27].…”
Section: Selection Of Evaluation Indicatorsmentioning
confidence: 99%
“…Most universities attempted to influence student behavior by encouraging them to participate in “top-down” activities such as internships programs (Hayles, 2019), cooking workshops (McDonough et al , 2014), mandatory sustainable activities (Felgendreher and Löfgren, 2018) and daily or long-term challenges (Bloodhart et al , 2013; Lambert and Cushing, 2017). However, the authors observed that the involvement of students was evident although it was not closely associated with the “bottom-up” approach as discussed by Mazon et al (2020). The outcomes (e.g.…”
Section: Resultsmentioning
confidence: 94%
“…Chen et al (2020) observed similar results in their study wherein they discussed how foreign exchange programs and involvement in various activities positively influenced the professional identity and career choice intentions of students. Finally, Browne et al (2020) demonstrated that student participation in local or regional projects positively influenced their PEB and critical thinking skills.…”
Section: Campus Operations On-campus Experiences and Outreach And Col...mentioning
confidence: 97%